Investigation of modern investment opportunities with cryptocurrency market: optimization - Chernova, Natalia; Serhiienko, Olena; Bril, Mykhailo; Bilotserkivskyi, Oleksandr; Kochorba, Valeriia (My University, 2024)
The research aim is to study effects of cryptocurrencies inclusion into an in vestment portfolio. To achieve the aim, portfolios with different composition of traditional and crypto assets are to be formed and compared. Methodology. It is proposed to conduct the following steps of the appropriate algorithm of investigating modern opportunities with cryptocurrency market: 1) preliminary analysis of the relationships and interdependencies between traditional assets and crypto assets; 2) formation of the initial set of crypto assets that can be potentially included into portfolio; 3) efficient frontier assessment for portfolios with different initial composition of assets; 4) comparative assessment and result analysis. Findings. The algorithm was implemented for the initial set of five most common traditional assets and ten cryptocurrencies. The latter constituents list was formed according to the value of market capitalization. Than the initial set of crypto assets was reduced according to their multidimensional distances from traditional assets. The results obtained allow to conclude that there are opportunities of portfolio efficiency increase via crypto assets inclusion in its structure. The increase value varies noticeably and depends on the particular kind of crypto assets, their total share and number. Originality. This research suggests to conduct additional preliminary procedures to choose potential candidates to be included into the traditional portfolio among initial set of crypto assets. Firstly, market capitalization value and low correlations with traditional portfolio constituents are taken into account. Secondly, all assets are presented as points in two-dimensional risk-return space and crypto assets are chosen according to the multidi mensional distance measure value.
Keywords: cryptocurrency; investment; portfolio; risk; return; optimization